net ionic equation:
SO₄²⁻ (aq) + Ba²⁺ (aq) → BaSO₄ (s)
Explanation:
We have the following chemical reaction:
H₂SO₄ (aq) + Ba(OH)₂ (aq) → BaSO₄ (s) + 2 H₂O (l)
Now we write the ionic equation:
2 H⁺ (aq) + SO₄²⁻ (aq) + Ba²⁺ (aq) + 2 OH⁻ (aq) → BaSO₄ (s) + 2 H⁺ + 2 OH⁻ (aq)
We remove the spectator ions to obtain the net ionic equation:
SO₄²⁻ (aq) + Ba²⁺ (aq) → BaSO₄ (s)
where we have:
(aq) - aqueous
(s) - solid
(l) - liquid
Learn more about:
net ionic equation
https://brainly.com/question/7018960
#learnwithBrainly